"Outline of the origin, foundation and development of landscape archeology" - Castillo Poveda, Manuel Alejandro (2016)
This paper presents the origin, foundation and development of the theoretical trend known as landscape archeology. The paper is based on a literature review of its historical construction, as well as the various influences that permeated this theoretical movement. Chronology, important figures, and philosophical, political as well as scientific points of views will be addressed in order to better understand this theoretical movement, its implications, the construction of a discourse and the fracture of the normative scheme of archaeological research.